2010
DOI: 10.1016/j.brainresbull.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal parathion exposure and interactions with a high-fat diet in adulthood: Adenylyl cyclase-mediated cell signaling in heart, liver and cerebellum

Abstract: Organophosphates are developmental neurotoxicants but recent evidence points to additional adverse effects on metabolism and cardiovascular function. One common mechanism is disrupted cell signaling mediated through cyclic AMP, targeting neurohumoral receptors, G-proteins and adenylyl cyclase (AC) itself. Earlier, we showed that neonatal parathion evokes later upregulation of the hepatic AC pathway in adolescence but that the effect wanes by young adulthood; nevertheless metabolic changes resembling prediabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
3
15
1
Order By: Relevance
“…Importantly, these effects are distinct from those of glucocorticoids, ruling out the possibility that they represent actions secondary to stress or disruption of the HPA axis. Further, the critical period, tissue selectivity and sex-specificity of the organophosphate effects on noradrenergic innervation seen here differ from those reported earlier for postsynaptic cell signaling [2,4,25,40]. Accordingly, hyperresponsiveness to hepatic gluconeogenic signals is not simply a compensation for presynaptic defects, nor are the effects on norepinephrine an adaptation to abnormalities in postsynaptic function.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Importantly, these effects are distinct from those of glucocorticoids, ruling out the possibility that they represent actions secondary to stress or disruption of the HPA axis. Further, the critical period, tissue selectivity and sex-specificity of the organophosphate effects on noradrenergic innervation seen here differ from those reported earlier for postsynaptic cell signaling [2,4,25,40]. Accordingly, hyperresponsiveness to hepatic gluconeogenic signals is not simply a compensation for presynaptic defects, nor are the effects on norepinephrine an adaptation to abnormalities in postsynaptic function.…”
Section: Discussioncontrasting
confidence: 85%
“…Developing animals appear to be even more sensitive, showing persistent and late-emerging metabolic abnormalities after otherwise nonsymptomatic, early-life exposures; these culminate in deficits in carbohydrate and lipid metabolism resembling prediabetes, and in sensitization to the adverse effects of elevated dietary fat intake [19,20,36,40,42]. We were able to show that one of the triggers for the metabolic effects was the emergence of abnormal hepatic cell signaling, reflecting a potentiation of gluconeogenic signals mediated by β-adrenergic receptors (βARs) and glucagon receptors [2,4,25,40]. Further, we found that the magnitude of the organophosphate effects on hepatic function were as large as those seen after comparable developmental exposures to the glucocorticoid, dexamethasone [3]; excess glucocorticoids are considered to be among the most definitive contributors to the cardiovascular and metabolic components comprising the “fetal origins of adult disease” [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…We recently conducted comparative studies of the effects of diazinon and parathion to elicit long-term changes in hepatic adenylyl cyclase, paralleling our work on chlorpyrifos [3740, 45]. We designed the dose regimens to produce a toxicodynamic match to the effects of chlorpyrifos, straddling the threshold for barely-detectable cholinesterase inhibition as the benchmark for dosing-equivalents.…”
Section: Diazinon Parathion and The Role Of Dietary Fat Intakementioning
confidence: 99%
“…Given recent concerns about human dietary choices, we focused on the role of saturated fat. In these studies, we exposed the animals to diazinon or parathion immediately after birth, using the same nonsymptomatic, low-level exposures as in our previous work; then, in adulthood, we switched half the animals to a diet where the 58% of the calories came from fat, and with a high proportion of saturated fat [4548]. Animals exposed to either of the organophosphates showed much greater weight gain on the high-fat diet than did unexposed animals given the same dietary manipulation, again in association with prediabetic metabolic profiles; this did not reflect differences in food consumption, indicating a difference in fat metabolism between the exposed and unexposed groups.…”
Section: Diazinon Parathion and The Role Of Dietary Fat Intakementioning
confidence: 99%
“…There is little known about possible mechanisms of long-term health effects of organophosphates, although laboratory studies provide some suggestive evidence. Rats exposed to organophosphates diazinon and parathion in the neonatal period demonstrated persistent changes in metabolism resembling prediabetes [137][138][139], and also exhibited greater weight gain on a high-fat diet compared with unexposed rats [139].…”
Section: Proposed Biological Mechanismsmentioning
confidence: 97%